Breast cancer in patients with high breast density by mammography - Bustamante Rodas, Liliana (2015)
Background: Breast density is associated with breast cancer risk and is considered as a biomarker in all mammograms. Studies quantify this risk but range varies widely due to types of population studied. Objective: To determine breast cancer risk in women with high breast density pattern as detected by mammography. Design: Retrospective case-control study. Setting: Department of Radiology, Hospital Nacional Edgardo Rebagliati Martins, Lima, Peru. Material: Mammograms. Methods: Between January 1 and December 31, 2008, we reviewed mammograms of 76 patients (cases) with diagnosis of breast cancer by Pathology Service; 152 controls corresponded to mammograms done during the same year and cataloged as BIRADS 1 and 2 without pathological study as informed by the Radiology Service. Tabar’s classification was used to determine the type of breast density. Main outcome measures: Breast density and breast cancer correlation. Results: Adjusted OR for age was 4.33 (95% CI 1.79 - 10.48), with p = 0.0006. The difference between frequencies of dense breasts in cases and controls was respectively 21.1% and 7.2% (Z = 2.8262, p = 0.0047). We encountered 38% of breast cancers occurring in patients ≥50 year-old and 19.3% in <50 year-old. There was higher percentage of non-dense breasts in both cases and controls age groups. Conclusions: Dense mammographic pattern significantly increased breast cancer risk.